Immigrants on Chinese Television and Limitations of China's Globalist Discourse. (January 2023) - Gan, Chun
Traditionally perceived as a country of emigration, China has in recent years become an increasingly popular subject for immigration and diaspora studies, with an immigrant population that has been growing quietly and steadily since the 1990s. However, media representations of immigrants in China have not garnered much attention. This article provides a critical assessment of how immigrants and immigrant experience are portrayed on Chinese television, using the example of Foreigner in China (2013–19), the first-ever program on a national platform to tackle this topic. It argues that, while the program paints a rather insightful and entertaining picture of contemporary immigrant life in China, its representation of immigrants is restricted by not only the internal contradiction of the Xi administration's globalist discourse, but also the exclusive, ethnocentric conception of Chinese nationhood, which remains the norm in a more heterogenous and globally conscious Chinese society.